Activity Diversification, Performance, And Profitability In Islamic Banking - Hilmy Baroroh (ITB AAS INDONESIA Surakarta, 2023)
Diversification of financing in Islamic banking is a strategy to improve performance. However, can the diversification of financing carried out by Islamic banks increase profitability? And is financing diversification able to reduce financing risks? The study wanted to prove these two theories by using data from the Islamic Banking Report for the 2016-2021 Period using the HHI indicator to diversify financing. Three categories of financing diversification are contract-based, financing-based, and economic sector-based. Profitability in the study was measured using the ROA ratio and the risk of bad debts with the NPF ratio. The result of this study is that the diversification of contract-based financing affects ROA in a negative direction and has a positive effect on NPF. On the other hand, financing diversification based on the use of financing does not affect increasing profitability and has a positive impact on the risk of bad debts. Meanwhile, sector-based financing diversification has a significant effect on increasing profitability and has a significant negative impact on reducing the risk of bad debts in Islamic banks.